2016
DOI: 10.14687/jhs.v13i3.3888
|View full text |Cite
|
Sign up to set email alerts
|

Understanding college student’s motivation for physical activity participation: The role of gender, sport type and activity level

Abstract: The present study aimed to investigate the motivational factors which has an influence on college students' participation in recreational physical activities. In this sense, gender, sport type (team or/and individual sport) and level of physical activity (MET scores) differences within motivational dimensions were examined. In the frame of the current study, a convenience sampling strategy was utilized. 383 Middle East Technical University students (Mage= 21.42, SD=3.30) voluntarily participated to this study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
1
2
0
1
Order By: Relevance
“…It makes sense that those who like to spend time with friends playing sports are also more likely to play together in a team and/or train together with them. These results are also consistent with previous studies in which team athletes had higher expectancies (Yazıcı, 2016 ) and cared more about affiliation (Molanorouzi et al, 2015 ). As peer relationships become more important from early to mid-adolescence, it would be interesting to find out in longitudinal studies whether the correlation between exercise behaviour and social EOEs also changes with age.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It makes sense that those who like to spend time with friends playing sports are also more likely to play together in a team and/or train together with them. These results are also consistent with previous studies in which team athletes had higher expectancies (Yazıcı, 2016 ) and cared more about affiliation (Molanorouzi et al, 2015 ). As peer relationships become more important from early to mid-adolescence, it would be interesting to find out in longitudinal studies whether the correlation between exercise behaviour and social EOEs also changes with age.…”
Section: Discussionsupporting
confidence: 92%
“…Also, male athletes report more perceived competence, self-esteem and physical self-worth than girls (Inchley et al, 2011 ). Therefore, it is not surprising that female adolescents are driven more by extrinsic motivation for sports compared to their male peers (Yazıcı, 2016 ). Furthermore, an older study found that girls choose to participate in sports more often because of social reasons while boys indicate reasons such as mastery and competitions (Eccles & Harold, 1991 ).…”
Section: Exercise-related Outcome Expectancies and Sport Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…Es por esto que se encuentran investigaciones que van direccionadas a identificar las necesidades de los deportistas universitarios, tal y como lo plantean Fernández y Quintero (2018), para sustentar la idea de entrenarlos en habilidades de rendimiento. En un estudio realizado por Yazici et al (2016) se encontró que los deportistas que practican deportes individuales, al estar fatigados académica y físicamente, disminuían sus niveles de motivación y con esto su sentido de pertenencia frente al deporte, mientras que los practicantes de deportes de conjunto mantienen sus niveles de motivación y compromiso con la práctica deportiva, por el hecho de sentirse parte de un grupo.…”
Section: Introductionunclassified